BANTUAN SUPERVISOR KEPADA GURU DALAM MENGATASI EMOSIONAL PROBLEM - MUHNIANSYAH ARASYID MAHANI (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
The life of a teacher is a unique experience that constantly grapples with complex problems. This is understandable because a teacher's life encompasses two realms: the school and the community, including the teacher's own family. Within these realms, teachers are inextricably linked to challenges that must be faced and resolved effectively. Furthermore, internal problems are sometimes, and can even be, more serious, and can have more serious consequences. From this description, it can be said that "emotional problems" are problems experienced by teachers, whether they are self-inflicted or caused by their environment. As supervisors, we not only supervise but also act as emotional companions for teachers, providing assistance in resolving these issues to create a healthy and conducive work climate within the school environment.